The effect of molar mass and degree of hydroxyethylation on the controlled shielding and deshielding of hydroxyethyl starch-coated polyplexes - Noga, Matthäus; Edinger, Daniel; Kläger, Raphaela; Wegner, Seraphine V.; Spatz, Joachim P.; Wagner, Ernst; Winter, Gerhard; Besheer, Ahmed (Biomaterials, 2013)
PEGylation is currently the gold-standard in shielding cationic DNA-polyplexes against non-specific interaction with blood components. However, it reduces cellular uptake and transfection, in what is known as the “PEG-dilemma”. In an approach to solve this problem we developed hydroxyethyl starch (HES)-shielded polyplexes which get deshielded under the action of alpha amylase (AA). In this study, the effect of molar mass and degree of hydroxyethylation on the shielding and deshielding of the polyplexes as well as their in vivo performance were investigated. For this purpose, a battery of HES-polyethylenimine (PEI) conjugates was synthesized, and their rate and extent of biodegradation were investigated using asymmetric flow-field flow fractionation (AF4) and quartz-crystal microbalance with dissipation (QCM-D). Additionally, the transfection efficiency of the polyplexes was tested in Neuro2A cells and tumor-bearing mice. AF4 and QCM results show a rapid degradation for HES with lower degrees of hydroxyethylation. Meanwhile, in vitro transfection experiments showed a better shielding for higher HES molar masses, as well as deshielding with a significant boost in transfection upon addition of AA. Finally, in vivo experiments showed that the biodegradable HES markedly reduced the non-specific lung transcription of the polyplexes, but maintained gene expression in the tumor, contrary to the non-degradable HES and PEG controls, which reduced both tumor and lung expression. This study shows that by controlling the molecular characteristics of HES it is possible to engineer the shielding and deshielding properties of the polyplexes for more efficient gene delivery.